Assessing the Risk of Prehospital Administration of Naloxone with Subsequent Refusal of Care. (2nd September 2016) - Levine, Michael; Sanko, Stephen; Eckstein, Marc
Abstract: Background: EMS providers frequently encounter opioid-toxic patients who receive naloxone and then refuse further medical care. Older studies revealed this practice to be safe. In light of the evolving patterns of opioid abuse, this study attempted to determine the safety of this practice.Methods: This is a retrospective review of all patient encounters by the Los Angeles Fire Department (LAFD) between July 1, 2011–December 31, 2013. All LAFD patient encounters are stored electronically. These electronic records were reviewed for subjects who received naloxone had a documented respiratory rate (RR) less than 12, and subsequently refused transport. Data abstracted included name, social security number (SSN), date of birth (DOB), date of EMS encounter, age, and treatment rendered. The names, SSN, and DOB, as available, were supplied to the coroner's office. The Coroner's records were reviewed to determine if a patient with the same or similar name (e.g., Jon vs. Jonathan) had died within 24 hours, 30 days, or 6 months of the initial EMS encounter. The abstractor was blinded to the study hypothesis.Results : 205 subjects were identified; the median (IQR) age was 41 (29-53) years. 27 (13%) were female. One subject (0.49%) died within 24 hours of the initial EMS encounter. The cause of death (COD) was coronary artery disease and heroin use. Two additional subjects (1. %) died within 30 days. One of these subjects died 6 days later; the COD is unknown. The other subject died 20 days after the EMS encounter; the COD was cardiovascular disease and liver cirrhosis. No additional subjects were identified at the 6 month follow up. A third subject died of a heroin overdose 16 months after the initial EMS encounter, but was beyond the pre-defined follow up period.Conclusions: The practice of receiving pre-hospital naloxone by paramedics and subsequently refusing care is associated with an extremely low short- and intermediate-term mortality. Despite an evolving pattern of opioid abuse, the results of this study are consistent with previously reported studies.